Male adolescent sexual assaulters: clinical observations - Awad, Awad G. (Journal of interpersonal violence, 1991)
Clinical assessments of 49 male adolescent sexual offenders who had sexually assaulted females their age or older showed that the majority were recidivists, had a history of antisocial behavior predating and coinciding with their sexual offenses, and came from a disturbed family background. Thirty-three percent of the offenders had a history of physical abuse in childhood, but, surprisingly, a history of sexual abuse could be confirmed in only two cases. The assaulters were less likely to be socially isolated than a comparison group of child molesters and more likely to socialize with older peers than a comparison group of delinquents. There was known sexual pathology in about 25% of the parents. Alcohol and drugs were not found to play a prominent role in the sexual assaults. Sexually deviant impulses and antisocial traits were found to be motivating factors for the majority of the assaults